Biochemical indices in the blood of rats at different terms of reparative osteogenesis in conditions of hyperhomocysteinaemia - Bezsmertniy, Yuriy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The effects, produced by hyperhomocysteinaemia (HHcy) and its correction with Decamevit and Glutargin on bone tissue metabolism in rats with femur fractures in different terms of reparative osteogenesis, were studied. It was established, that HHcy caused enhancement of bone tissue resorption, increase of calcium excretion with urine, inhibition of collagen biosynthesis in rats with femur fractures. HHcy induced dysregulation of reparative osteogenesis by lowering the transforming growth factor beta -1 (TGF- β1) levels in the first 2 weeks after trauma and by an excessive increase of this index on days 30-45 after the trauma. Decamevit and Glutargin reduced HHcy-induced imbalance between the processes of resorption and biosynthesis of bone tissue, and normalized the staging changes of TGF- β1 levels in blood serum of rats with femur fractures.